Do Aspirin and Other Antiplatelet Drugs Reduce the Mortality in Critically Ill Patients?. (9th November 2011) - Lösche, Wolfgang; Boettel, Janina; Kabisch, Björn; Winning, Johannes; Claus, Ralf A.; Bauer, Michael
Abstract : Platelet activation has been implicated in microvascular thrombosis and organ failure in critically ill patients. In the first part the present paper summarises important data on the role of platelets in systemic inflammation and sepsis as well as on the beneficial effects of antiplatelet drugs in animal models of sepsis. In the second part the data of retrospective and prospective observational clinical studies on the effect of aspirin and other antiplatelet drugs in critically ill patients are reviewed. All of these studies have shown that aspirin and other antiplatelet drugs may reduce organ failure and mortality in these patients, even in case of high bleeding risk. From the data reviewed here interventional prospective trials are needed to test whether aspirin and other antiplatelet drugs might offer a novel therapeutic option to prevent organ failure in critically ill patients.